Cómo el uso del software administrativo puede satisfacer las necesidades de los comerciantes que no hacen parte de la economía digital (2022)
The wood industry in El Retiro, especially the sector dedicated to the manufacture of furniture, has meant for this municipality a fundamental factor for the development of its culture, economy and identity. In view of this representativeness, it was decided to carry out this research with the objective of developing a marketing plan to internationalize this activity and promote it worldwide, taking advantage of the human potential that the locality has, and given the lack of knowledge in foreign trade. topic and other aspects related to the importance of raw materials and the export of ready-made products.